Urgent care medicine : Questions you will be asked. Top secrets in urgent care / Robert Olympia, Rory O'Neill, Matthew Silvis - Olympia, Robert
I have been a fan of the Secrets Series since medical school. I love the simplicity of the question and answer format and value the depth of medical knowledge each page holds. I remember using each of the Secret Series specialty books during every rotation of medical school, helping me to answer questions while on rounds, to research the diagnosis of an undifferentiated patient, or to prepare for in-training and board examinations. Throughout my career, the Secrets Series has been a large part of my professional life. I was blessed to be involved with the first, and subsequent, editions of Pediatric Emergency Medicine Secrets and, more recently, used Pediatric Secrets to successfully pass my recertification examination. Our department uses both the Emergency Medicine Secrets and Pediatric Emergency Medicine Secrets books as required reading for the medical student rotation.